Copper(II), Nickel(II), Cobalt(II), and Iron(II) complexes of conjugated organic ligands as potential dye-sensitised solar cell materials / Anita Marlina - Anita, Marlina (2015)
The primary aim of this research was to synthesize and characterize metals(II) complexes of conjugated organic ligands as potential dye-sensitised solar cell materials. The ligands were synthesized from the reactions of 2,6-diamino-4-phenyl-1,3,5-triazine with pyrrole-2-carboxaldehyde (H2L1), 2,5-thiophenedicarboxaldehyde (H2L2), 2,5-thiophenedicarboxylic acid (H2L3), and acetylenedicarboxylic acid (H2L4). These complexes were formed from the reactions of the ligands with metal(II) ethanoates ([M2(CH3COO)4] and metal(II) hexadecanoates ([M(CH3(CH2)14COO)4]), where M = Cu(II), Ni(II), Co(II), and Fe(II). A total of 32 complexes were successfully synthesized and fully characterised. The structures of these complexes were deduced from CHN microanalyses, FTIR spectroscopy and UV-vis spectroscopy. Their magnetic properties were determined at room temperature by the Gouy method, their optical bandgaps were deduced by electronic spectroscopy (UV- visible and fluorescence spectroscopy), the lifetimes of their excited complexes were determined by fluorescence spectroscopy, and finally their thermal and mesomorphic properties by thermogravimetry (TG), differential scanning calorimetry (DSC), and polarising optical microscopy (POM). {[Ni2(CH3(CH2)14COO)4(L4)]}n was diamagnetic, while all other complexes were paramagnetic. The geometries for all complexes depend on the metal(II) ion, namely octahedral, square pyramidal and square planar. The decomposition temperatures of all complexes were in the range 142 °C – 255 °C. The optical bandgaps of these complexes obtained from the absorption spectroscopy were in the range of 3.4 eV – 3.8 eV, while the values obtained from the emission spectroscopy were in the range of 1.7 eV – 2.1 eV. The lifetimes of the excited complexes were in the range of 2.4 ns – 3.4 ns. Complexes with ligands L3 and L4 exhibited mesomorphisms.